Translation techniques used in translating a smartphone user manual - Mustafa, Faisal; Aziz, Zulfadli A; Khabri, Ihsanul (Universitas Islam Negeri Banda Aceh, 2021)
As many smartphones are imported from overseas and the user manuals are written in English, the translation of a user manual is, therefore, very important for the Indonesian customers whose English is not their second language. Good translation results are then very essential in order that the customers understand the information easily and clearly. The focus of this research is the bilingual English-Indonesian Samsung’s GT-19500 user manual. This research aims to find translation techniques applied in the book. In this descriptive research, the sentences were the tokens that were recorded in Microsoft Excel. The tokens were then analyzed based on the categories of translation techniques in question. It was found that there were nine translation techniques used in the user manual. The translation techniques used in Samsung’s GT-19500 user manual are borrowing (41%), literal translation (25%), calque (13%), transposition (7%), equivalence (6%), adaptation (5.3%), modulation (3%), and omission (2%). Therefore, the techniques used in translating a smartphone user manual are unique to this type of document because the document consists of many terms without Indonesian equivalence.